2013
DOI: 10.1590/s0100-06832013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Composição lignocelulósica e isótopica da vegetação e da matéria orgânica do solo de uma turfeira tropical: I - composição florística, fitomassa e acúmulo de carbono

Abstract: RESUMOA matéria orgânica do solo (MOS) é um dos grandes reservatórios de carbono (C) da Terra e constitui um dos principais componentes do ciclo do C. Turfeiras, ambientes acumuladores de MOS, são produto da decomposição de vegetais, que se desenvolvem e se acumulam em ambientes saturados com água, sendo o estádio inicial da sequência de carbonificação. A fitomassa participa de forma marcante no ciclo global do C, armazenando em torno de 85 % de todo o C terrestre acima do solo. O tecido vegetal é composto pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
7
0
10
Order By: Relevance
“…The Histosols that make up the peatlands are usually found in flooded depressions, and are colonized by wet grassland (WGL) and semi-deciduous forest (SDF) vegetation types, both from the Cerrado biome (Campos et al, 2010;Silva et al, 2013a).…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The Histosols that make up the peatlands are usually found in flooded depressions, and are colonized by wet grassland (WGL) and semi-deciduous forest (SDF) vegetation types, both from the Cerrado biome (Campos et al, 2010;Silva et al, 2013a).…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
“…In addition, the higher content of lignin in woody species compared to herbaceous species leads to greater resistance to decomposition of the OM (Moreira et al, 2006; Potes et al, 2010), hence, its greater accumulation. Silva et al (2013a) quantified lignin and cellulose in the species found in greatest abundance in the peatlands from the SdEM and they obtained the highest contents in woody species.…”
Section: Characterization Of Organic Matter and Soil Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…O elevado conteúdo de matéria orgânica (MO) confere a esses solos características contrastantes em relação aos solos minerais, principalmente quanto ao alumínio, que comumente forma complexos estáveis com ampla variedade de grupos funcionais, como os grupos carboxílicos, fenólicos, enólicos, alcoólicos, entre outros (Silva & Mendonça, 2007;Kempter & Frenzel, 2008;Silva et al, 2012a). A forma como o Al se liga a esses compostos pode variar consideravelmente, o que resulta em maior ou menor estabilidade de ligação, que inclui ligações por pontes de hidrogênio, atração eletrostática, troca de ligantes e quelação Kempter & Frenzel, 2008;Silva & Mendonça, 2007 (trocável) é a predominante (Silva & Mendonça, 2007;Motta & Melo, 2009;Silva et al, 2012b).…”
Section: Introductionunclassified